2022
DOI: 10.1016/j.resmer.2021.100880
|View full text |Cite
|
Sign up to set email alerts
|

Progression to a severe form of COVID-19 among patients with chronic respiratory diseases

Abstract: Rationale Viral respiratory infections, including SARS-CoV-2 infection, can trigger respiratory symptoms among patients suffering from chronic respiratory diseases, leading to exacerbations and hospitalizations. Despite the tropism of SARS-CoV-2 into the respiratory tract, chronic respiratory diseases do not seem to be risk factors for severe forms of COVID-19. Objectives To assess whether hospitalized patients for COVID-19 with chronic respiratory diseases were at lowe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 37 publications
1
3
0
Order By: Relevance
“…“Reversed halo” sign was not present in the patients with COPD. In regards to the severity score, our results are concordant with those by Basin S. et al [ 41 ]. In detail, the referenced study reported CT1 category of 63.1% vs. 42.4%; CT2 category, 26.2% vs. 40.2%; CT3 category, 9.2% vs. 15.0%; CT4 category (more than 75%), 1.5% vs. 3.3% in COPD vs. non-COPD group, respectively.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…“Reversed halo” sign was not present in the patients with COPD. In regards to the severity score, our results are concordant with those by Basin S. et al [ 41 ]. In detail, the referenced study reported CT1 category of 63.1% vs. 42.4%; CT2 category, 26.2% vs. 40.2%; CT3 category, 9.2% vs. 15.0%; CT4 category (more than 75%), 1.5% vs. 3.3% in COPD vs. non-COPD group, respectively.…”
Section: Discussionsupporting
confidence: 92%
“…Similar results are demonstrated by Gemicioglu B. et al, lower ALC (1.42 ± 0.77 × 109/L), higher WBC (10.6 ± 5.2 × 109/L) and ANC (7.94 ± 4.18 × 109/L), with the median level of NLR 8.09 ± 7.25 [ 32 ]. In contrast, Basin S. et al observed no significant differences in the level of leukocytes and lymphocytes in patients with COPD vs. control group (6.4 × 109/L vs. 6.5 × 109/L and 1.0 vs. 0.9 × 109/L, respectively) [ 41 ]. Such heterogeneities in the results might be due to differences in the severity of the disease among included patients in different studies.…”
Section: Discussionmentioning
confidence: 99%
“…Coronavirus disease might also influence other organs. Thus, the associated comorbidities of COVID-19 include many more chronic diseases, such as lung [ 40 ] and kidney [ 41 ] disorders. It should be noted that the long-term consequences of the infection are still not yet known; consequently, the other undesirable effects might be revealed with time.…”
Section: Introductionmentioning
confidence: 99%
“…We read with interest the work of Sarah Basin et al [1] . who are to be congratulated for their counter intuitive insight into the assessment of risk in patients with chronic respiratory diseases and we fully agree with them when they conclude that this category of patients is under-represented among those who will present the most severe forms of Covid 19.…”
mentioning
confidence: 99%